2003
DOI: 10.1103/physreva.67.063202
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the femtosecond-resolved photoelectron spectrum of the NO molecule

Abstract: The effect of laser fields on the NO interaction potentials is obtained by the calculation of time-resolved photoelectron spectrum ͑TRPES͒ using the time-dependent wave-packet method. The calculation not only shows that the overlap of the pump-probe pulses makes some NO molecular ''invisible'' states visible, but also that the coupling strength and the positions of relevant curves change on increasing the laser intensity. These changed potentials affect their dynamical behavior and influence the shape and posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…In our calculations, the HHG and the attosecond pulse can be investigated by solving the time-dependent Schrödinger equation (TDSE) [30][31][32][33][34][35][36][37][38] based on single-active electron approximation. In the dipole approximation and the length gauge, the TDSE is given by,…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…In our calculations, the HHG and the attosecond pulse can be investigated by solving the time-dependent Schrödinger equation (TDSE) [30][31][32][33][34][35][36][37][38] based on single-active electron approximation. In the dipole approximation and the length gauge, the TDSE is given by,…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Since the LMI affects the status of molecules, it must influence the population in each molecular state. In fact, through analyzing the photoelectron spectrum and photodissociation absorption spectrum, one can deduce the population easily [12,17]. In this paper, we will first write out the Hamiltonian of the molecule in intense laser fields.…”
Section: Introductionmentioning
confidence: 99%
“…Besides above, other methods, such as PIC (particle-in-cell) method [10], the tensor density matrix theory [11], etc., are also used to interpret LMI. Recently, it is noticed that as a powerful tool to study the quantum reactive scattering of chemical reactions, timedependent wavepacket (TDWP) method [12][13][14] has been successfully applied to simulate the quantum dynamics of the ultrafast photoionization and photodissociation of some diatomic molecules in intense laser fields [15][16][17][18]. It is found that when the perturbation theory is not valid in this case, the TDWP method shows its advantages in both the time-saving and the flexibility to deal with LMI.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28] In the dipole approximation and the length gauge, the TDSE is given by (atomic units are used throughout this paper unless stated otherwise)…”
Section: Computational Aspectsmentioning
confidence: 99%